THE STUDY OF THE USE OF POPULAR NOVELS TO IMPROVE READING INTEREST AND ENGLISH PROFICIENCY - Cynantia Rachmijati; Anita Anggraeni (JOALL (Journal of Applied Linguistics and Literature), 2019)
AbstractThe aim of the study "The study of the use of popular novels to improve reading interest and English proficiency" is to find out how teachers, parents and students views on popular novels especially KKPK and Teen Lit novels. KKPK and Teen-Lit novels are easily available anywhere and favored by children and adolescents are interesting topic to study The research method is descriptive qualitative. The results show that the novels have many positive impacts. In terms of language, help to develop language and vocabulary. In terms of emotions, help to develop emotional intelligence. In terms of English, help students to learn the structure of sentences and apply them in social media. To increase reading interest, any subject of reading will be better for students while performed it regularly with parents or teachers, without any disruption such as gadgets or television.    Keywords: KKPK, teen-lit,novels, reading interest, English proficiency